2018
DOI: 10.2196/games.9530
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence for the Outcomes of Therapeutic Video Games for Adolescents With Anxiety Disorders: Systematic Review

Abstract: BackgroundExtant evidence suggests that the proportion of adolescents suffering from anxiety disorders (ADs) has increased by up to 70% since the mid-1980s, with experience of anxiety at this stage associated with significant negative short- and long-term life outcomes. The existing therapeutic interventions (eg, cognitive behavioral therapy, CBT; attention bias modification, ABM) have proven to have clinically measurable benefits in reducing anxiety, but their efficacy is often compromised by social and pract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 53 publications
3
37
0
1
Order By: Relevance
“…Nevertheless, these studies have varied methodologies, which remain a limitation in the process of evaluating such games in a therapeutic context. Our results are in line with those from previous meta-analyses and literature reviews on serious games, which also found no consensus on which type of control group is the best to evaluate such games (26,64). The same issue occurs for the evaluation of commercially available video games.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, these studies have varied methodologies, which remain a limitation in the process of evaluating such games in a therapeutic context. Our results are in line with those from previous meta-analyses and literature reviews on serious games, which also found no consensus on which type of control group is the best to evaluate such games (26,64). The same issue occurs for the evaluation of commercially available video games.…”
Section: Discussionsupporting
confidence: 89%
“…Not surprisingly, there is a growing body of literature that explores the advantages of playing digital games among players in different age groups, particularly in terms of improving attention span, memory, and problem-solving skills [ 32 ]; enhancing the ability of gamers to cope with failure [ 32 ] and manage emotions [ 32 ]; improving information retention [ 33 ]; facilitating deep learning [ 34 ]; supporting and promoting behavior change [ 35 ]; and promoting socialization [ 32 ]. Moreover, evidence suggests that games can be effectively used as therapeutic tools to support recovery from anxiety, depression, posttraumatic stress disorder (PTSD), and other disorders [ 36 - 42 ]. Finally, youths and primary care providers have identified video game technology as a valuable tool for early intervention and treatment [ 30 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews and meta-analyses that assess the accessibility, feasibility, and effectiveness of serious video games for use in mental health have been published [ 36 - 42 ]. However, these reviews focused on specific mental health conditions, mainly depression and anxiety [ 36 - 42 ], without reporting on other mental illnesses affecting youths, such as psychosis, eating disorders, and substance misuse. Moreover, some of these reviews assessed the effectiveness of digital games for mental health in mixed-age populations, which often included older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, novel research has focused on the impact of commercial games as health interventions, psychotherapy tools for assessment, and in teaching social skills [7]. In addition, a few reviews have been published to evaluate the effectiveness of video game technology in the treatment of different mental health conditions (eg, depression and anxiety) [8-10].…”
Section: Introductionmentioning
confidence: 99%